Nano-structure Bi (at) BiOBr / TiO2 composite material as well as preparation method and application thereof

By uploading Bi quantum dots on BiOBr/TiO2 composite materials, the spectral response range is broadened, and the problem of insufficient utilization of composite photocatalysts on near-infrared light is solved, and efficient catalytic degradation effect under visible and near-infrared light is achieved, and photocatalytic is improved. Active and natural light utilization.

CN119215940APending Publication Date: 2024-12-31BEIFANG UNIV OF NATITIES +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411347390.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Existing composite photocatalysts can only produce catalytic effects under visible light and cannot utilize near-infrared light, resulting in poor photocatalytic performance.

Method used

The nanostructured Bi@BiOBr/TiO2 composite material is composed of BiOBr/TiO2 heterojunction composite material and loaded Bi quantum dots. By regulating the size of Bi quantum dots and the absorption band edge, the spectral response range is broadened to make it in visible light and near Infrared light can effectively catalyze the degradation of organic pollutants.

Benefits of technology

The photocatalytic activity and natural light utilization rate are improved, and the effective degradation of organic pollutants under weak light sources is achieved. The process flow is short, the energy consumption is low, and the photocatalytic performance is efficient and stable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119215940A_ABST
    Figure CN119215940A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of semiconductor composite materials, and particularly relates to a nano-structure Bi (at) BiOBr / TiO2 composite material as well as a preparation method and application thereof. The composite material is composed of a BiOBr / TiO2 heterojunction composite material and Bi quantum dots loaded on the BiOBr / TiO2 heterojunction composite material, the absorption band edge is 1.1-1.6 eV, and the spectral response range is widened from visible light to a near-infrared light region. According to the preparation method disclosed by the invention, the addition ratio of NaBH4, the surfactant and BiOBr / TiO2 is utilized, the reduction reaction rate is regulated and controlled, the controllable growth of the size of the Bi quantum dots and the controllable synthesis of a nano structure are realized, the precise regulation and control of the light absorption threshold of the composite material are further realized, and the minimum absorption band edge of the composite material is controlled. A reduction method is adopted for one-step reduction synthesis at normal temperature, the technological process is short, energy consumption is low, the reaction process is short, energy consumption is low, and the dosage of organic reagents is small.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of semiconductor composite material technology, specifically relating to a nanostructured Bi@BiOBr / TiO2 composite material, its preparation method, and its application. Background Technology

[0002] Photocatalysis is a technology that, under irradiation by a light source of a specific wavelength, excites electrons in the valence band of a semiconductor to the conduction band, thereby leaving free electrons (e) in both the conduction and valence bands of the semiconductor. - ) and holes (h + Electrons and holes can be captured by O2, H2O, etc., to generate superoxide radicals (·O2) with strong redox properties. - ) and hydroxyl radicals (·OH); these highly reactive substances with strong redox properties can further mineralize organic matter into small molecules such as H2O and CO2, or solidify CO2 to form organic products. The spectral response range, photoelectron-hole separation rate, and transfer rate of a photocatalyst are the most important factors affecting its photocatalytic performance. Bismuth oxybromine (BiOBr) has a unique layered structure with a band gap of approximately 2.90 eV and responds to visible light. However, in single-phase BiOBr, photogenerated electrons... - h + It has a fast recombination rate, low mobility, low effective utilization of natural light, and poor photocatalytic performance.

[0003] In the prior art, Chinese invention patent application number 201711114706.0 discloses a silver iodide nanoparticle-modified bismuth oxybromide composite photocatalyst, its preparation method, and its application. This composite photocatalyst uses bismuth oxybromide as a support, with silver iodide nanoparticles modified onto the bismuth oxybromide. The preparation method includes the following steps: dispersing bismuth oxybromide in water, adding silver nitrate solution and potassium iodide for a co-precipitation reaction to obtain the silver iodide nanoparticle-modified bismuth oxybromide composite photocatalyst. Although the material prepared by this method can promote charge separation to some extent, due to its band structure limitations, it can only produce catalytic activity under visible light and cannot utilize near-infrared light. Summary of the Invention

[0004] Based on this, this application provides a nanostructured Bi@BiOBr / TiO2 composite material, its preparation method, and its application, in order to solve the technical problem that existing composite photocatalysts can only produce catalytic effects under visible light and cannot utilize near-infrared light.

[0005] The technical solution of the present invention to solve the above-mentioned technical problems is as follows:

[0006] A nanostructured Bi@BiOBr / TiO2 composite material, characterized in that it is composed of a BiOBr / TiO2 heterojunction composite material and Bi quantum dots loaded thereon, wherein the absorption band edge of the nanostructured Bi@BiOBr / TiO2 composite material is 1.1 to 1.6 eV.

[0007] Preferably, the above-mentioned nanostructured Bi@BiOBr / TiO2 composite material has Bi quantum dot sizes of 19 to 39 nm.

[0008] A method for preparing a nanostructured Bi@BiOBr / TiO2 composite material includes the following steps:

[0009] S10. Add sodium borohydride and surfactant to water and stir until fully dissolved to obtain solution A;

[0010] S20. Add the BiOBr / TiO2 heterojunction composite material to the solution A to form a mixed suspension B;

[0011] S30. The mixed suspension B is allowed to stand and age for a specified time to obtain a nanostructured Bi@BiOBr / TiO2 composite material precipitate;

[0012] S40. The precipitate of the nanostructured Bi@BiOBr / TiO2 composite material is washed with deionized water and anhydrous ethanol until neutral, and then dried to obtain the nanostructured Bi@BiOBr / TiO2 composite material.

[0013] Preferably, in step S10 of the above-mentioned method for preparing the nanostructured Bi@BiOBr / TiO2 composite material, the surfactant includes at least one of polyethylene glycol, polyvinylpyrrolidone, sodium dodecylbenzenesulfonate, and sodium dodecyl sulfate.

[0014] Preferably, in the preparation method of the above-mentioned nanostructured Bi@BiOBr / TiO2 composite material, in step S10, the concentration of the surfactant in solution A is 5 to 125 g·L⁻¹. -1 .

[0015] Preferably, in the preparation method of the above-mentioned nanostructured Bi@BiOBr / TiO2 composite material, in step S10, the addition ratio of sodium borohydride to water is (0.1 to 1.0) mmol:10 mL.

[0016] Preferably, in the above-mentioned method for preparing the nanostructured Bi@BiOBr / TiO2 composite material, the mass ratio of sodium borohydride to the BiOBr / TiO2 heterojunction composite material is (22 to 57):(500 to 1000).

[0017] Preferably, in the preparation method of the above-mentioned nanostructured Bi@BiOBr / TiO2 composite material, in step S20, the ratio of the BiOBr / TiO2 heterojunction composite material to the solution A is (0.2 to 0.5) g: 10 mL.

[0018] Preferably, in the above-mentioned method for preparing the nanostructured Bi@BiOBr / TiO2 composite material, the specified time in step S30 is ≥2h.

[0019] A nanostructured Bi@BiOBr / TiO2 composite material is prepared by the above-mentioned method. The Bi quantum dot size of the composite material is 19 to 39 nm, the absorption band edge is 1.1 to 1.6 eV, and the structure is a three-dimensional "bird's nest" shaped nanostructure.

[0020] Application of a nanostructured Bi@BiOBr / TiO2 composite material as described above in the photocatalytic degradation of organic pollutants.

[0021] The present invention adopts the above technical solution, and its beneficial effects are as follows:

[0022] 1. The nanostructured Bi@BiOBr / TiO2 composite material of the present invention is composed of a BiOBr / TiO2 heterojunction composite material and Bi quantum dots loaded thereon. The absorption band edge of the nanostructured Bi@BiOBr / TiO2 composite material is 1.1 to 1.6 eV. An appropriate amount of Bi quantum dots can improve the light absorption range and utilization rate of the composite material, that is, improve the photocatalytic activity and spectral response range under visible light. The minimum absorption band edge of the nanostructured Bi@BiOBr / TiO2 composite material of this scheme is 1.14 eV, compared with 2.72 eV of the prior art BiOBr / TiO2, broadening the spectral response range from visible light to the near-infrared region, thereby enabling catalytic degradation under weak light sources.

[0023] 2. The nanostructured Bi@BiOBr / TiO2 composite material of the present invention belongs to the nanostructured semiconductor heterojunction composite material. This composite material greatly increases the photogenerated carrier yield and utilization rate, that is, improves the utilization rate of natural light.

[0024] 3. The preparation method of the nanostructured Bi@BiOBr / TiO2 composite material of the present invention utilizes the addition ratio of NaBH4, surfactant and BiOBr / TiO2 to regulate the reduction reaction rate, thereby achieving controllable growth of Bi quantum dot size and controllable synthesis of three-dimensional "bird's nest" shaped nanostructure, and thus achieving precise control of the light absorption threshold of the nanostructured Bi@BiOBr / TiO2 composite material, thereby controlling the minimum absorption band edge of the composite material.

[0025] 4. The preparation method of the nanostructured Bi@BiOBr / TiO2 composite material of the present invention adopts a reduction method for one-step reduction synthesis at room temperature, which has a short process flow, low energy consumption, short reaction flow, low energy consumption, and low amount of organic reagents. Attached Figure Description

[0026] Figure 1 The images show the XRD patterns of the nanostructured Bi@BiOBr / TiO2 composite material synthesized in this invention, and the XRD patterns of the comparative BiOBr / TiO2 composite material.

[0027] Figure 2 The images show SEM images of the nanostructured Bi@BiOBr / TiO2 composite material synthesized in this invention, where (a) are SEM images of the BiOBr / TiO2 raw materials used directly in all cases; and (b) are SEM images of the nanostructured Bi@BiOBr / TiO2 composite material in Experimental Example 1.

[0028] Figure 3 These are the photodegradation curves of the nanostructured Bi@BiOBr / TiO2 composite materials synthesized in Experimental Examples 1 to 4 of this invention for organic pollutants (a) ciprofloxacin and (b) methylene blue under visible light.

[0029] Figure 4 This is the photocatalytic cyclic degradation curve of ciprofloxacin by the nanostructured Bi@BiOBr / TiO2 composite material synthesized in Experimental Example 1 of this invention. Detailed Implementation

[0030] It should be noted that, unless otherwise specified, the embodiments and features described in the embodiments of the present invention can be combined with each other. The technical solutions of the present invention will be further described below with reference to the accompanying drawings of the embodiments of the present invention. The present invention is not limited to the following specific embodiments.

[0031] In one specific embodiment of this application, a nanostructured Bi@BiOBr / TiO2 composite material is provided, comprising a BiOBr / TiO2 heterojunction composite material and Bi quantum dots loaded thereon. The absorption band edge of the nanostructured Bi@BiOBr / TiO2 composite material is 1.1 to 1.6 eV. Further, the Bi quantum dots have a size of 19 to 39 nm and are uniformly embedded in the heterojunction composite material. The nanostructured Bi@BiOBr / TiO2 composite material of this embodiment has quantum dot sizes of 19 to 38.5 nm and an absorption band edge of 1.14 to 1.6 eV. The minimum absorption band edge is 1.14 eV, compared to 2.72 eV for BiOBr / TiO2, broadening the spectral response range from the visible light region to the near-infrared region, improving the utilization rate of near-infrared light, thereby enabling catalytic degradation even under weak light sources.

[0032] In another specific embodiment of this application, a method for preparing a nanostructured Bi@BiOBr / TiO2 composite material includes the following steps:

[0033] S10. Add sodium borohydride and surfactant to water and stir until fully dissolved to obtain solution A. In this scheme, any reducing-resistant surfactant can be used, preferably at least one of polyethylene glycol, polyvinylpyrrolidone, sodium dodecylbenzenesulfonate, and sodium dodecyl sulfate. If the amount of NaBH4 and surfactant added is too small, the target product, the nanostructured Bi@BiOBr / TiO2 composite material, cannot be synthesized; if the amount added is too large, the target product cannot be synthesized and the reaction efficiency is low. Therefore, in a preferred embodiment, the concentration of surfactant in solution A is 5 to 125 g·L⁻¹. - The ratio of sodium borohydride to water is (0.1 to 1.0) mmol: 10 mL.

[0034] S20. The BiOBr / TiO2 heterojunction composite material is added to solution A to form a mixed suspension B. Preferably, the mass ratio of sodium borohydride to the BiOBr / TiO2 heterojunction composite material is (22 to 57):(500 to 1000), and the ratio of the BiOBr / TiO2 heterojunction composite material to solution A is (0.2 to 0.5) g:10 mL. The BiOBr / TiO2 heterojunction composite material is a semiconductor heterojunction, which can effectively broaden the spectral response range, improve the utilization rate of natural light, promote the separation of photogenerated electrons and holes, prolong the carrier lifetime, and greatly improve the photocatalytic activity of single-phase photocatalysts under natural light. The presence of Bi can introduce new energy levels in BiOBr, forming a metal-semiconductor contact interface. This interface is beneficial to improving photocatalytic efficiency and photocatalytic stability, especially in the near-infrared region. Experiments show that when the Bi quantum dot size is 38.1 nm and the absorption band edge is 1.58 eV, the degradation rate of ciprofloxacin is 90.51% after 60 min of irradiation, and the degradation rate of methylene blue is 94.31% after 180 min of irradiation. When the Bi quantum dot size is 19.9 nm and the absorption band edge is 1.14 eV, which is in the near-infrared region, the degradation rates of ciprofloxacin and methylene blue remain at a high level, with a degradation rate of 84.91% for ciprofloxacin after 60 min of irradiation and 86.24% for methylene blue after 180 min of irradiation.

[0035] S30. The mixed suspension B is allowed to stand and age for a specified time to obtain a nanostructured Bi@BiOBr / TiO2 composite material precipitate; the specified aging time is ≥2h, and further 2 to 5h.

[0036] S40. The precipitate of the nanostructured Bi@BiOBr / TiO2 composite material is washed with deionized water and anhydrous ethanol until neutral, and then dried to obtain the nanostructured Bi@BiOBr / TiO2 composite material.

[0037] For example, the preparation method of nanostructured Bi@BiOBr / TiO2 composite materials includes the following steps:

[0038] Sodium borohydride and a surfactant were placed in water and stirred thoroughly to obtain a reducing solution A. The BiOBr / TiO2 heterojunction composite material was added to solution A to form a mixed suspension B. The mixed suspension B was stirred until homogeneous and allowed to stand for at least 2 hours to obtain a nanostructured Bi@BiOBr / TiO2 composite material precipitate. This precipitate was washed with deionized water and anhydrous ethanol until neutral, and then dried to obtain the target product, the nanostructured Bi@BiOBr / TiO2 composite material. The XRD pattern of this material is shown below. Figure 1 .

[0039] It is worth noting that the process temperature and process time involved in the above embodiments are all temperatures or times used in the experiment. Any reasonable adjustments made by those skilled in the art based on the process temperature and process time provided by the present invention, within the error range, should be included within the protection scope of the present invention.

[0040] The following specific experimental examples further illustrate the technical solution and technical effects of the present invention.

[0041] 1. Main reagents

[0042] It should be noted that in the embodiments of the present invention, all reagents and solvents are commercially available and can be used without further purification.

[0043] 2. Preparation of nanostructured Bi@BiOBr / TiO2 composite materials

[0044] 2.1 Comparative Example

[0045] The BiOBr / TiO2 heterojunction composite material in the existing technology was used as a comparison in the experiment.

[0046] 2.2 Experimental Example 1

[0047] 0.8 mmol of sodium borohydride and 1.0 g of polyvinylpyrrolidone (PVP K30) were placed in 20 mL of water and stirred thoroughly to obtain a reducing solution A. 0.5 g of BiOBr / TiO2 heterojunction composite material was added to solution A to form a mixed suspension B. The mixed suspension B was stirred until homogeneous and allowed to stand for 3 h to obtain the nanostructured Bi@BiOBr / TiO2 composite material precipitate. The precipitate was washed with deionized water and anhydrous ethanol until neutral and then dried to obtain the target nanostructured Bi@BiOBr / TiO2 composite material.

[0048] 2.3 Experimental Example 2

[0049] 0.6 mmol of sodium borohydride and 0.7 g of polyethylene glycol (PEG10000) were placed in 20 mL of water and stirred thoroughly to obtain a reducing solution A. 0.8 g of BiOBr / TiO2 heterojunction composite material was added to solution A to form a mixed suspension B. The mixed suspension B was stirred until homogeneous and allowed to stand for 5 h to obtain the nanostructured Bi@BiOBr / TiO2 composite material precipitate. The precipitate was washed with deionized water and anhydrous ethanol until neutral and then dried to obtain the target nanostructured Bi@BiOBr / TiO2 composite material.

[0050] 2.4 Experimental Example 3

[0051] 1.5 mmol of sodium borohydride and 2.5 g of sodium dodecylbenzenesulfonate were placed in 20 mL of water and stirred thoroughly to obtain a reducing solution A. 1.0 g of BiOBr / TiO2 heterojunction composite material was added to solution A to form a mixed suspension B. The mixed suspension B was stirred until homogeneous and allowed to stand for 3 h to obtain the nanostructured Bi@BiOBr / TiO2 composite material precipitate. The precipitate was washed with deionized water and anhydrous ethanol until neutral, and then dried to obtain the target nanostructured Bi@BiOBr / TiO2 composite material.

[0052] 2.5 Experimental Example 4

[0053] 1.0 mmol of sodium borohydride and 0.1 g of polyvinylpyrrolidone (PVP K30) were placed in 20 mL of water and stirred thoroughly to obtain a reducing solution A. 0.5 g of BiOBr / TiO2 heterojunction composite material was added to solution A to form a mixed suspension B. The mixed suspension B was stirred until homogeneous and allowed to stand for 2 h to obtain the nanostructured Bi@BiOBr / TiO2 composite material precipitate. The precipitate was washed with deionized water and anhydrous ethanol until neutral and then dried to obtain the target nanostructured Bi@BiOBr / TiO2 composite material.

[0054] 3. Performance Analysis of Nanostructured Bi@BiOBr / TiO2 Composite Materials

[0055] 3.1 Structural Analysis of Nanostructured Bi@BiOBr / TiO2 Composite Material

[0056] The BiOBr / TiO2 heterojunction composite material prepared in this application is as follows: Figure 2 As shown in the figure, Bi quantum dots are uniformly embedded in the heterojunction composite material. It can be seen that after adding sodium borohydride, Bi... 3+ Part of it is reduced to elemental Bi, and the nanostructured Bi@BiOBr / TiO2 heterojunction composite material forms a three-dimensional "bird's nest" shaped nanostructure.

[0057] 3.2 Photocatalytic Activity Analysis of Nanostructured Bi@BiOBr / TiO2 Composite Material

[0058] Ciprofloxacin and methylene blue were selected as photocatalytic degraders of pollutants, and their photocatalytic degradation performance was tested on the samples in the experiment. The light source was a 500W xenon lamp with a wavelength λ≥420nm. The Bi quantum dot size, light absorption threshold, and photocatalytic activity of the nanostructured Bi@BiOBr / TiO2 composite materials synthesized in different experimental examples are shown in Table 1.

[0059] Table 1. Size, absorption threshold, and photocatalytic activity of Bi quantum dots in nanostructured Bi@BiOBr / TiO2 composite materials.

[0060]

[0061] Please refer to Table 1. By changing the addition ratio of NaBH4, surfactant, and BiOBr / TiO2, the size of Bi quantum dots, light absorption threshold, and photocatalytic activity of the nanostructured Bi@BiOBr / TiO2 composite material can be controlled. The photodegradation effects of the nanostructured Bi@BiOBr / TiO2 composite material on ciprofloxacin and methylene blue in the experimental examples of this application are as follows: Figure 3 As shown, under visible light irradiation, the Bi quantum dot size of the nanostructured Bi@BiOBr / TiO2 composite material in Experimental Example 1, with an absorption band edge of 1.58 eV, showed a degradation efficiency of 90.51% for ciprofloxacin after 60 min of irradiation and 94.31% for methylene blue after 180 min of irradiation. The Bi quantum dot size of the nanostructured Bi@BiOBr / TiO2 composite material in Experimental Example 4, with an absorption band edge of 1.14 eV (near-infrared region), maintained a high degradation rate for both ciprofloxacin and methylene blue, achieving a degradation rate of 84.91% for ciprofloxacin after 60 min of irradiation and 86.24% for methylene blue after 180 min of irradiation.

[0062] 3.3 Stability Analysis of Nanostructured Bi@BiOBr / TiO2 Composites

[0063] Figure 4 The cyclic photocatalytic degradation curves of the nanostructured Bi@BiOBr / TiO2 composite photocatalyst show that after four cycles, the nanostructured Bi@BiOBr / TiO2 composite still exhibits high photocatalytic performance, maintaining a degradation efficiency of over 70% for ciprofloxacin. This indicates that the photocatalytic performance of the nanostructured Bi@BiOBr / TiO2 composite is stable, making it a composite photocatalyst with high degradation efficiency and good reusability.

[0064] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation of the present invention. Those skilled in the art can make other variations or modifications based on the above description. It is neither necessary nor possible to exhaustively describe all embodiments here. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A nanostructured Bi@BiOBr / TiO2 composite material, characterized in that: The nanostructured Bi@BiOBr / TiO2 composite material is composed of a BiOBr / TiO2 heterojunction composite material and Bi quantum dots loaded thereon. The absorption band edge of the nanostructured Bi@BiOBr / TiO2 composite material is 1.1 to 1.6 eV.

2. The nanostructured Bi@BiOBr / TiO2 composite material according to claim 1, characterized in that: The Bi quantum dots of the nanostructured Bi@BiOBr / TiO2 composite material have a size of 19 to 39 nm.

3. A method for preparing a nanostructured Bi@BiOBr / TiO2 composite material, characterized in that: The following steps are involved: S10. Add sodium borohydride and a surfactant to water and stir until fully dissolved to obtain a solution A; S20. The BiOBr / TiO2 heterojunction composite material is added to the solution A to form a mixed suspension B; S30. The mixed suspension B is allowed to stand and aged for a specified time to obtain a nanostructured Bi@BiOBr / TiO2 composite material precipitate; S40. The Bi@BiOBr / TiO2 composite material precipitate is washed with deionized water and anhydrous ethanol until it becomes neutral, and then dried to obtain the nanostructured Bi@BiOBr / TiO2 composite material.

4. The method for preparing the nanostructured Bi@BiOBr / TiO2 composite material according to claim 3, characterized in that: In step S10, the surfactant includes at least one of polyethylene glycol, polyvinyl pyrrolidone, sodium dodecylbenzene sulfonate, and sodium dodecyl sulfate.

5. The method for preparing the nanostructured Bi@BiOBr / TiO2 composite material according to claim 3, characterized in that: In step S10, the concentration of the surfactant in the solution A is 5 to 125 g·L -1 .

6. The method for preparing the nanostructured Bi@BiOBr / TiO2 composite material according to claim 3, characterized in that: In step S10, the addition ratio of sodium borohydride to water is (0.1 to 1.0) mmol:10 mL.

7. The method for preparing the nanostructured Bi@BiOBr / TiO2 composite material according to claim 3, characterized in that: The mass ratio of the sodium borohydride to the BiOBr / TiO2 heterojunction composite material is (22 to 57):(500 to 1000).

8. The method for preparing the nanostructured Bi@BiOBr / TiO2 composite material according to claim 3, characterized in that: In step S20, the ratio of the BiOBr / TiO2 heterojunction composite material to the solution A is (0.2 to 0.5) g:10 mL.

9. The method for preparing the nanostructured Bi@BiOBr / TiO2 composite material according to claim 3, characterized in that: In step S30, the designated time is ≧2h.

10. Use of the nanostructured Bi@BiOBr / TiO2 composite material as claimed in claim 1 in photocatalytic degradation of organic pollutants.